2018
DOI: 10.1002/pld3.77
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines delay leaf maturation in low‐alkaloid tobacco varieties

Abstract: The development of low-alkaloid (LA) tobacco varieties is an important target in the tobacco breeding industry. However, LA Burley 21 plants, in which the Nic1 and Nic2 loci controlling nicotine biosynthesis are deleted, are characterized by impaired leaf maturation that leads to poor leaf quality before and after curing. K E Y W O R D Sethylene, inhibition of biosynthesis, maturation, nic1/nic2 mutation, nicotine, ornithine

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 67 publications
2
22
0
1
Order By: Relevance
“…It may also be important to study the potential for increased insect herbivory on tobacco plants with reduced nicotine accumulation, as increased insect feeding has been observed on Nicotiana plants with silenced nicotine biosynthetic genes (Steppuhn et al, 2004). Nolke et al (2018) reported increases in polyamine content to be correlated with delays in maturation and senescence in a study of nic1/nic2 isolines of burley tobacco, with problems being most apparent in the lowest alkaloid material. Delayed field ripening of tobacco can translate into reduced cured leaf quality.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
“…It may also be important to study the potential for increased insect herbivory on tobacco plants with reduced nicotine accumulation, as increased insect feeding has been observed on Nicotiana plants with silenced nicotine biosynthetic genes (Steppuhn et al, 2004). Nolke et al (2018) reported increases in polyamine content to be correlated with delays in maturation and senescence in a study of nic1/nic2 isolines of burley tobacco, with problems being most apparent in the lowest alkaloid material. Delayed field ripening of tobacco can translate into reduced cured leaf quality.…”
Section: Combining Bbl Mutations With Recessive Alleles At the Nic1 Amentioning
confidence: 99%
“…Low nicotine content tobacco has the side-effect of aberrant leaf maturation which in turn leads to inferior product quality. As analyzed previously (Nölke et al, 2018) et al 2000). Downregulation of PMT or PR50 genes led to lower nicotine levels in tobacco (Kudithipudi & Hayes, 2018).…”
Section: Discussionmentioning
confidence: 75%
“…The phenotype of the transgenic plants was compared to WT plants grown under the same cultivation conditions in the greenhouse. Using the ripening markers that we established before (Nölke et al, 2018), we confirmed that the leaf maturation was disturbed in these lines as the transgenic plants had significantly higher (Kudithipudi & Hayes, 2018).…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations